Luminescence, chiroptical, magnetic and ab initio crystal-field characterizations of an enantiopure helicoidal Yb(iii) complex. Issue 4 (10th November 2020) - Gendron, Frédéric; Di Pietro, Sebastiano; Abad Galán, Laura; Riobé, François; Placide, Virginie; Guy, Laure; Zinna, Francesco; Di Bari, Lorenzo; Bensalah-Ledoux, Amina; Guyot, Yannick; Pilet, Guillaume; Pointillart, Fabrice; et al.
Abstract : The electronic structure of a chiral Yb(iii )-based complex is fully determined by taking advantage of experimental magnetic, luminescence, and chiroptical (NIR-ECD and CPL) characterizations in combination with ab initio wavefunction calculations. Abstract : The electronic structure of a chiral Yb(iii )-based complex is fully determined by taking advantage of experimental magnetic, luminescence, and chiroptical (NIR-ECD and CPL) characterizations in combination with ab initio wavefunction calculations. The combined use of these techniques allows determining with high resolution the electronic structure diagram as well as the nature of the different states involved in the magnetic and chiroptical properties of the investigated complex. The crystal-field picture deduced from spectroscopic measurements (absorption and emission) is used to reproduce the magnetic properties. Subsequently, advanced ab initio calculations demonstrate that global chiroptical spectra correspond to the sum of entangled transitions with similar or opposite polarizations.